Gold-catalyzed 1,2-oxyalkynylation of N-Allenamides with ethylnylbenziodoxolones - Banerjee, Somsuvra; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2019)
A gold-catalyzed 1,2-oxyalkynylation of N-allenamides with ethylnylbenziodoxolones (EBXs) has been achieved for the first time. The reaction, which follows a redox-neutral Au(I)/Au(III) catalytic pathway, was enabled in an attempt to exhaust the EBX reagents atom-economically by putting the nucleophilic carboxylate part of EBXs to appropriate use. This constitutes the first example for gold-catalyzed beta-alkynylation of N-allenamides to construct highly valuable 1,3-enynes. The potential of the sequence is further documented by some follow-up transformations.

Gold-catalyzed alkynylative meyer-schuster rearrangement - Banerjee, Somsuvra; Ambegave, Shivhar B.; Mule, Ravindra D.; Senthilkumar, Beeran; Patil, Nitin T. (Organic Letters, 2020)
By applying the ``interplay'' mode, which consolidates two key reactivity modes of gold catalysis, namely pi-activation mode and cross-coupling mode, the first alkynylative Meyer-Schuster rearrangement is designed and successfully implemented. The current protocol gives straightforward access to enynones, a highly valuable building block, from easily available propargyl alcohol feedstocks. Control experiments suggest an Au(III) catalyst triggers the Meyer-Schuster rearrangement, whereas monitoring the reaction with ESI-HRMS provided strong evidence in favor of a key alkynylgold(III) intermediate which supports the proposed ``interplay'' scenario.